Associated Factors of Anxiety among Acute Coronary Syndrome Patients in Kelantan and Terengganu - Wan Adnan, Wan Nor Asyikeen; Ab Hamid, Siti Azrin; Sulong, Zatul Rathiah; Fauzi, Mohd Hashairi (Mazandaran University of Medical Sciences, 2017)
Background and purpose: Anxiety is a common condition among acute coronary syndrome patients. This syndrome often goes unrecognised and can persist for months to years, while impacting substantially the quality of life. Therefore, this study aimed to identify the associated factor of anxiety among acute coronary syndrome patients in Hospital Universiti Sains Malaysia and Hospital Sultanah Nur Zahirah. Materials and Methods: This cross-sectional study involved acute coronary syndrome patients admitted to Hospital Universiti Sains Malaysia, Kelantan and Hospital Sultanah Nur Zahirah, Terengganu between August 2014 and May 2015. A standardised questionnaire was developed to interview the respondents. The questionnaire was separated into two sections. The first section comprised the socio-demographic details of the patients. The second section was the validated Depression Anxiety Stress Scale 21 (DASS-21) questionnaire. Simple and multiple logistic regressions were used for analysing the collected data. Results: The mean (standard deviation (SD)) age of acute coronary syndrome patients was 60.4 (11.3) years and 61.2 (10.4) years in Hospital Universiti Sains Malaysia and Hospital Sultanah Nur Zahirah respectively. The majority of acute coronary syndrome patients who experienced anxiety were male (86.3%) with 84.9% of them Malay ethnicity and 85.9% of them married. The factor associated with anxiety among acute coronary syndrome patients was having a history of ischemic heart disease (adjusted odd ratio (OR): 2.20, as well as confidence interval (CI): 1.19, 4.10, p=0.013). Conclusion: It was concluded that anxiety had myriad effects on cardiovascular physiology, which plays an important role in the increased incidence of ischemic events in patients. A screening tool should be created to refine and identify the psychological status of acute coronary syndrome patients, so that early treatment could be given.